2013
DOI: 10.1093/nar/gks1464
|View full text |Cite
|
Sign up to set email alerts
|

Nap1 regulates proper CENP-B binding to nucleosomes

Abstract: CENP-B is a widely conserved centromeric satellite DNA-binding protein, which specifically binds to a 17-bp DNA sequence known as the CENP-B box. CENP-B functions positively in the de novo assembly of centromeric nucleosomes, containing the centromere-specific histone H3 variant, CENP-A. At the same time, CENP-B also prevents undesired assembly of the CENP-A nucleosome through heterochromatin formation on satellite DNA integrated into ectopic sites. Therefore, improper CENP-B binding to chromosomes could be ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 68 publications
(58 reference statements)
0
21
1
Order By: Relevance
“…Since crystal or NMR structure of G4 DNAzyme remains unexplored, we performed molecular docking and dynamics simulation by using AutoDock and NAMD programs to understand the hemin-binding micro-environment of G4 DNAzymes (4749). As shown in Figure 5, hemin stacks well upon the 3′-G-quartet of Dz-00 and Dz-11.…”
Section: Resultsmentioning
confidence: 99%
“…Since crystal or NMR structure of G4 DNAzyme remains unexplored, we performed molecular docking and dynamics simulation by using AutoDock and NAMD programs to understand the hemin-binding micro-environment of G4 DNAzymes (4749). As shown in Figure 5, hemin stacks well upon the 3′-G-quartet of Dz-00 and Dz-11.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, to date, 3 out of 8 cases of described pseudodicentric neocentric chromosomes in humans occur on the Y chromosome (Marshall et al, 2008) where centromere re-activation is predicted to be less frequent due to lack of CENP-B. Previous reports have suggested that CENP-B is removed from non-centromeric regions via its chaperone Nap1 (Tachiwana et al, 2013). Considering our findings, such regulation appears also to be important to prevent CENP-B-driven centromere formation outside of alpha-satellite DNA.…”
Section: Discussionmentioning
confidence: 99%
“…formation of human artificial chromosomes or HACs) ( 9 , 10 ). HOR units are enriched with a 17-bp binding motif for centromere protein B (CENP-B box) that is required for de novo kinetochore formation as well as for prevention of CENP-A nucleosome assembly at ectopic chromosomal sites ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%